Knowledge Management Maturity Assessment in Air Drilling Associates using G-KMMM - Dana I. Sensuse; Richard Vinc; Ricky Nauvaldy Ruliputra; Siti Hadjar; Jonathan Sofian Lusa; Pudy Prima (Proceeding of the Electrical Engineering Computer Science and Informatics, 2018)
Since the early 1990s, companies in the oil & gas industry have realized that their business operations are knowledge-based, where company performance can be derived from faster identification, an assessment of an opportunity, and the speed of an exploitation. The oil & gas industry is one of the leading industries in the application and development of knowledge management; this is caused by changes in market and technology from 1990s to the beginning of the 21st century. Utilizing knowledge management is a must to be able to compete with other oil and gas industry companies. Currently, Air Drilling Associates (ADA) as one of the companies in oil & gas industry already has implemented knowledge management system, but its benefits are far from the expectation. In order to position their efforts and initialize knowledge management, companies need framework to use as a template. The objective of this paper is to measure the knowledge management maturity of Air Drilling Associates and other suggestion related to knowledge management for improvement.